Synthesis and Study Biological Activity of Some New Substituted Thiazolidin-4-one Derivatives - Abdulhussein, Nooralhuda M.; Abood, Zeid Hassan (Iraqi Journal of Science, 2024)
The microwave (MW) method was used to create a series of new thiazolidin-4-one derivatives containing benzothiazole and azo groups. Azoaldehyde derivative A was synthesized via the coupling reaction of 2-aminobenzothiazole diazonium ions and 2-hydroxybenzaldehyde. The resultant azoaldehyde A was then subjected to condensation reactions with the primary aromatic amines using the MW method to give azoimines derivatives S1-S5. Finally, compounds S1-S5 were reacted with α-mercaptoacetic acid by the MW method to generate the thiazolidin-4-one derivatives T1-T5. The novel-produced compounds T1-T5 were identified by FT-IR, 1H NMR, and 13C NMR spectroscopy. The DPPH was used to determine the antioxidant activity of the novel-produced compounds T1-T5. The obtained results for T1 and T5 were excellent as antioxidants in comparison with ascorbic acid, while in the antibacterial study, it was discovered that T2, T3, and T5 were found to be more successful than Gentamycin as a control drug against Staphylococcus aureus in an antibacterial investigation, while T3 was found to be more effective than the reference drug against Escherichia coli.